Evolutionary and biogeographical support for species-specific proteins in lizard chemical signals. (29th September 2021) - Mangiacotti, Marco; Baeckens, Simon; Scali, Stefano; Martín, José; Van Damme, Raoul; Sacchi, Roberto
Abstract: The species-specific components of animal signals can facilitate species recognition and reduce the risks of mismatching and interbreeding. Nonetheless, empirical evidence for species-specific components in chemical signals is scarce and mostly limited to insect pheromones. Based on the proteinaceous femoral gland secretions of 36 lizard species (Lacertidae), we examine the species-specific component potential of proteins in lizard chemical signals. By quantitative comparison of the one-dimensional electrophoretic patterns of the protein fraction from femoral gland secretions, we first reveal that the protein composition is species specific, accounting for a large part of the observed raw variation and allowing us to discriminate species on this basis. Secondly, we find increased protein pattern divergence in sympatric, closely related species. Thirdly, lizard protein profiles show a low phylogenetic signal, a recent and steep increase in relative disparity and a high rate of evolutionary change compared with non-specifically signal traits (i.e. body size and shape). Together, these findings provide support for the species specificity of proteins in the chemical signals of a vertebrate lineage.